In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Féminisme et réaction masculiniste au Québec - Dupuis-Déri, Francis (Dialogues sur la troisième vague du féminisme, 2005)
Dialogues sur la troisième vague féministe rassemble des voix qui, chacune à sa manière, propose des pistes de réflexion quant à la nature des changements qui affectent le féminisme québécois. Ces dialogues explorent des thématiques liées au pouvoir, à la sexualité et à l'image du corps, liées à la mondialisation, aux conflits générationnels, au backlash, et à la relation entre la théorie, la pratique et la culture populaire."--Couverture.
Keywords: 1900-1999; 1990-1999; antiféminisme; approches et analyses; corps; cours; discipline; discours dominant; fem1000; histoire et politique; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sexualité; systèmes d'oppressions; thématiques; violences; études culturelles